2013
DOI: 10.3390/ijerph10104967
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Underweight, Overweight and Obesity among Women and Children: Results from the 2011 Uganda Demographic and Health Survey

Abstract: While undernutrition and infectious diseases are still persistent in developing countries, overweight, obesity, and associated comorbidities have become more prevalent. Uganda, a developing sub-Saharan African country, is currently experiencing the public health paradox of undernutrition and overnutrition. We utilized the 2011 Uganda Demographic and Health Survey (DHS) to examine risk factors and hot spots for underweight, overweight, and obesity among adult females (N = 2,420) and their children (N = 1,099) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
60
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 29 publications
(36 reference statements)
4
60
0
1
Order By: Relevance
“…16,17 Further, because of the rapid pace of development in Uganda, prevalence of risk factors may be quickly changing and may be especially increasing in urban areas. Prior research has found higher rates of obesity 3,14,18,19 and diabetes 19 among urban children or adults in sub-Saharan Africa. Although risk factors such as physical activity and sleep are not as well studied in the region, research in China, 20 Haiti, 21 and Brazil 22 has suggested that rural-urban differences may exist in sleep quality or deprivation, and research in Cameroonian adults has found lower activity levels in urban dwellers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 Further, because of the rapid pace of development in Uganda, prevalence of risk factors may be quickly changing and may be especially increasing in urban areas. Prior research has found higher rates of obesity 3,14,18,19 and diabetes 19 among urban children or adults in sub-Saharan Africa. Although risk factors such as physical activity and sleep are not as well studied in the region, research in China, 20 Haiti, 21 and Brazil 22 has suggested that rural-urban differences may exist in sleep quality or deprivation, and research in Cameroonian adults has found lower activity levels in urban dwellers.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Overweight among adult women has been found to be related to living in urban areas and being in the highest wealth class. 14 Although population-based surveys have assessed weight status and nutritional factors in adults and children younger than 5, 7,11 few studies have measured weight status and related factors in school-aged youth. One, which surveyed youth in both Uganda and Ghana, found that 10.4% and 3.2% of female and male adolescents were overweight 15 but was unable to report on many potentially confounding factors such as socioeconomic status, rural/urban status, and sleep.…”
Section: Introductionmentioning
confidence: 99%
“…), obesity (Turi et al . ) and create eco‐epidemiological models to analyse gene–environmental interactions (Torbick et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…La estrategia europea Horizon2020 (European Commission 2014) es una muestra significativa del aumento de la importancia de las IES y de la necesidad de comprender, gestionar, planificar y apoyar la toma de decisiones eficaz en el sector de la educación superior. Sin embargo, el actual ritmo acelerado de creación y almacenamiento de datos conlleva que la extracción de valor añadido sea un proceso complejo (Turi et al 2013). Asimismo, los datos geoespaciales también han seguido esta tendencia y están ganando importancia convirtiéndose en big data por derecho propio, dando paso a la big geo-data (Sui 2014).…”
Section: Introductionunclassified